The Implementation of AIDS Care Community (ACC) Work Program as an Efforts for Handling HIV / AIDS Cases in Poncol Community Health Center Work Area - Wafah, Siti Ekfiyatil; Husodo, Besar Tirto; Handayani, Novia (Faculty of Public Health, Universitas Diponegoro, Semarang, Indonesia, 2021)
Introduction: Semarang City has the highest number of HIV / AIDS cases in Central Java. Several attempts to control HIV / AIDS cases, such as the organization for AIDS that is named after AIDS Care Community (ACC) in every village scope. The purpose of this study is to describe the implementation of the ACC program in Poncol Community Health Center.Methods: This is a descriptive research, uses qualitative methods using in-depth interview for data collection techniques. There are 9 informants who are selected by using purposive sampling method. Data is analyzed using descriptive method. The process of data analysis begins with collecting data, and then reducing the data that has been generated. After that, the data are presented and concluded.Results: The results show that the implementation of ACC program in the work area of Poncol Community Health Center is assisted by Poncol Puskesmas. There is 1 ACC out of 9 ACC that is actively implementing the ACC program while the others are not running well. It is found that low capacity of ACC members, lack of funds, low of support from the local government (village), low community support, inadequate facilities and infrastructure that affect the implementation of ACC programs. Therefore, the output is not achieved optimally.Conclusions: The implementation of the of the ACC program in Poncol Community Health Center work area has not been running optimally. Support from all parties is needed, including from the members of the ACC, local government, AIDS commission, and the community in order to achieve the ACC goals.